2019
DOI: 10.1158/1535-7163.mct-18-0464
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A, a Novel Natural Compound to Target PI3K/AKT/mTOR Pathway in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy and is highly resistant to standard treatment regimens. Targeted therapies against KRAS, a mutation present in an overwhelming majority of PDAC cases, have been largely ineffective. However, inhibition of downstream components in the KRAS signaling cascade provides promising therapeutic targets in the management of PDAC and warrants further exploration. Here, we investigated Urolithin A (Uro A), a novel natural compound derived from pomegranat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…Inhibitors of PI3K reduced tumor burden through limiting recruitment of immunosuppressive components including MDSCs and Treg cells in tumors (11,37,38). In this study, we revealed that Pik3ip1, a critical regulator of PI3K, serves as an essential rheostat for T-cell-mediated immunity, which sets the threshold for T-cell responses under homeostatic conditions and neoantigen exposure, especially tumor antigen stimulation.…”
Section: Discussionmentioning
confidence: 74%
“…Inhibitors of PI3K reduced tumor burden through limiting recruitment of immunosuppressive components including MDSCs and Treg cells in tumors (11,37,38). In this study, we revealed that Pik3ip1, a critical regulator of PI3K, serves as an essential rheostat for T-cell-mediated immunity, which sets the threshold for T-cell responses under homeostatic conditions and neoantigen exposure, especially tumor antigen stimulation.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, it is plausible that there is a close link between the anti-cancer effects of urolithins and AHR antagonism in humans. However, other mechanisms for urolithin-mediated anti-cancer effects have been proposed [64], such as PI3K/AKT/mTOR [65] and AR receptor [66]. Further in vivo studies are certainly required for assessing the ability of urolithins to control human tumor growth, and the role of AHR in mediating these effects.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the anticancer action of UA through the inhibition of AKT and p70S6K phosphorylation, reduction of proliferation, and enhancement of cellular apoptosis has been confirmed in both xenograft and transgenic mouse models of pancreatic cancer. Additionally, UA treatment has reprogrammed the tumor microenvironment, as evidenced by reduced levels of infiltrating immunosuppressive cell populations such as myeloid-derived suppressor cells, tumor-associated macrophages, and regulatory T-cells thus inhibiting tumor growth resulting in enhanced survival[ 58 ].…”
Section: Othersmentioning
confidence: 99%